(untitled) (PROKLA. Journal of Critical Social Science, 2005)
Famous utopias as well as the 20th century dystopias and contemporary science fiction designs are reviewed. The social background of these conceptions as well as the ideas of society and the use and meaning of technology incorporated in these utopias are discussed in favour to support a discussion about the construction of future societies.